Drug Abuse from Social Work Perspectives - Singh, Paramjit Singh Jamir; Azman, Azlinda; Durairaja, Shankar; Rashadiah, Thajun; Yee, Lim May (Asian Social Work Journal, 2024)
Social work plays a crucial role in restoring societal functions. This paper advocates for integral theory as a defining framework for the identity of social work. In the context of Malaysia, a nation characterized by its multicultural landscape and grappling with a two-century-long issue of drug abuse, the application of integral theory becomes particularly relevant. Through an in-depth case study, this paper aims to illustrate the practicality and efficacy of integral theory in addressing the complex challenges posed by drug abuse in Malaysia. The discussion delves into various facets, including social identities, ego development, ethnopharmacology, and the political climate of Malaysia, providing a comprehensive understanding of the ongoing drug abuse issue. By examining these elements, the paper seeks to underscore how integral theory can serve as a transformative lens for social work in Malaysia. Crucially, this exploration contends that integral theory is not merely a practical tool for establishing the identity of social work; it should also be regarded as the future trajectory of social work. As societal issues evolve, the holistic and inclusive approach offered by integral theory positions social work to effectively navigate the complexities and nuances inherent in addressing drug abuse and other pressing challenges in the years to come.